2021
DOI: 10.1186/s13054-021-03494-9
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm echodensity in mechanically ventilated patients: a description of technique and outcomes

Abstract: Background Acute increases in muscle sonographic echodensity reflect muscle injury. Diaphragm echodensity has not been measured in mechanically ventilated patients. We undertook to develop a technique to characterize changes in diaphragm echodensity during mechanical ventilation and to assess whether these changes are correlated with prolonged mechanical ventilation. Methods Diaphragm ultrasound images were prospectively collected in mechanically v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
0
23
1
1
Order By: Relevance
“…On the other hand, it is possible that changes in echodensity may depend on the accumulation fluid resuscitation-related tissue edema [16] . At variance with previous studies [18] , we found that changes in echodensity of both muscles were significantly related to a positive fluid balance. This may reflect the different patient population and the peculiar characteristics of COVID-19 patients, in whom endothelial activation and dysfunction play a key role in the pathogenesis of the disease, by altering the integrity of vessel barrier and potentially favouring fluid extravasation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it is possible that changes in echodensity may depend on the accumulation fluid resuscitation-related tissue edema [16] . At variance with previous studies [18] , we found that changes in echodensity of both muscles were significantly related to a positive fluid balance. This may reflect the different patient population and the peculiar characteristics of COVID-19 patients, in whom endothelial activation and dysfunction play a key role in the pathogenesis of the disease, by altering the integrity of vessel barrier and potentially favouring fluid extravasation.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, muscle mass and quality was assessed using ultrasound; indeed, rectus femoris echodensity, as a marker of muscle quality, increased over the first week by on average 12%, which is similar to prior published data [ 16 , 17 , 31 , 48 , 49 ]. More recently, changes in diaphragm echodensity during the early course of mechanical ventilation were described and associated to a negative outcome [18] . In both cases, the changes increments in muscle echodensity are presumed to be the consequence of either inflammation or infection, or edema due to fluid shifts in the context of volume resuscitation with a positive fluid balance [54] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Images were saved in JPEG format and echogenicity was quantified using a greyscale histogram analysis of the images. The analysis was performed with ImageJ software ( https://imagej.nih.gov/ij/index.html; NIH, Bethesda, MD, USA), using the square method to define the region of interest for analysis using the histogram function, selecting a free-form area devoid of artefacts [ 25 , 26 ]. Images were reviewed by a second reader (VC) who was not directly involved in imagine acquisition.…”
Section: Methodsmentioning
confidence: 99%